Tonic Firing Rate Controls Dendritic Ca(2+) Signaling and Synaptic Gain in Substantia Nigra Dopamine Neurons - Hage, Travis A. (J Neurosci, 2015)
Substantia nigra dopamine neurons fire tonically resulting in action potential backpropagation and dendritic Ca(2+) influx. Using Ca(2+) imaging in acute mouse brain slices, we find a surprisingly steep relationship between tonic firing rate and dendritic Ca(2+). Increasing the tonic rate from 1 to 6 Hz generated Ca(2+) signals up to fivefold greater than predicted by linear summation of single spike-evoked Ca(2+)-transients. This “Ca(2+) supralinearity” was produced largely by depolarization of the interspike voltage leading to activation of subthreshold Ca(2+) channels and was present throughout the proximal and distal dendrites. Two-photon glutamate uncaging experiments show somatic depolarization enhances NMDA receptor-mediated Ca(2+) signals >400 μm distal to the soma, due to unusually tight electrotonic coupling of the soma to distal dendrites. Consequently, we find that fast tonic firing intensifies synaptically driven burst firing output in dopamine neurons. These results show that modulation of background firing rate precisely tunes dendritic Ca(2+) signaling and provides a simple yet powerful mechanism to dynamically regulate the gain of synaptic input.